A prospective observational study on post-operative major surgical patients developing silent deep vein thrombosis at Hospital Universiti Sains Malaysia - Pak Kai, Wong (2014)

(untitled)
Introduction: Silent deep vein thrombosis (DVT) is one of the life-threatening complications affecting surgical patients. So far there is only one study documenting the incidence of silent DVT in Malaysia. Besides, no efforts have been made to evaluate the use of Caprini risk assessment model to identify subjects who are in need of prompt DVT prophylaxis. Objectives: The aims of this study are to determine the incidence of silent DVT and evaluate the potential utility of Caprini risk assessment model to target high risk subjects for DVT prophylaxis. Methods: This is a prospective cohort study involving 55 HUSM surgical subjects who are at risk of silent DVT. Each subject had a preoperative and postoperative compression ultrasound complemented by duplex venous ultrasonography of deep venous system performed by two separate radiologists. Caprini risk assessment scores were calculated for each study participants and the decision on the administration of DVT prophylaxis was made based on the clinical judgement of the clinicians in charge without knowing the calculated Caprini risk scores. The association between DVT prophylaxis and Caprini risk scores were analysed using simple logistic regression. Any p value that is less than 0.05 is considered statistically significant. Results: Not a single subject developed DVT (incidence rate of silent DVT = 0%, n=0). There is a significant association between DVT prophylaxis and Caprini risk scores (OR 8.16 (95% CI: 1.01, 68.74), p value = 0.008). Besides, the use of central venous catheter is also significantly associated with the use of DVT prophylaxis (OR 6.34 (95% CI: 1.62, 24.80), p value = 0.016). Interestingly the use of central venous catheter resulted in more than 4 point increment of Caprini risk scores (mean increment: 4.186 (95% CI: 3.164, 5.207), p value <0.001) instead of the usual 2 points allotted to this risk factor. Conclusion: Silent DVT is virtually non-existent in this study setting. The judicious use of DVT prophylaxis, which is guided by the inadvertent use of Caprini risk score during dayto- day practice, may explain the effective prevention of silent DVT at this setting. Nevertheless, further studies are warranted to further characterize the utility of Caprini risk assessment scores for the prediction of silent DVT in this setting.